2017
DOI: 10.1038/ncomms13924
|View full text |Cite
|
Sign up to set email alerts
|

Syntrophic anaerobic photosynthesis via direct interspecies electron transfer

Abstract: Microbial phototrophs, key primary producers on Earth, use H2O, H2, H2S and other reduced inorganic compounds as electron donors. Here we describe a form of metabolism linking anoxygenic photosynthesis to anaerobic respiration that we call ‘syntrophic anaerobic photosynthesis'. We show that photoautotrophy in the green sulfur bacterium Prosthecochloris aestaurii can be driven by either electrons from a solid electrode or acetate oxidation via direct interspecies electron transfer from a heterotrophic partner b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(54 citation statements)
references
References 36 publications
1
44
1
Order By: Relevance
“…143 or (F) intercellular nanotubes that allow an exchange of cytoplasmic contents. 145,147 Moreover, also (G) flagella-like structures 67,148 or (H) a direct surface contact 149,150 can facilitate the exchange of metabolites between cells. of outer membrane material (i.e.…”
Section: Mechanisms Of Metabolite Transfermentioning
confidence: 99%
“…143 or (F) intercellular nanotubes that allow an exchange of cytoplasmic contents. 145,147 Moreover, also (G) flagella-like structures 67,148 or (H) a direct surface contact 149,150 can facilitate the exchange of metabolites between cells. of outer membrane material (i.e.…”
Section: Mechanisms Of Metabolite Transfermentioning
confidence: 99%
“…It has previously been considered that DIET is primarily restricted to environments in which Geobacter species are abundant [8][9][10][11][12] , because Geobacter species are the only microbes in pure culture that have been definitively shown to function as electron-donating partners for DIET 9,[13][14][15][16][17] . Studies with Geobacter metallireducens have suggested that electrically conductive pili (e-pili) are an important conduit for electron transfer from the electron-donating partner 9,14,17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…(ii) DIET has been proposed to control methane release [4][5][6]. (iii) A recent finding indicates that DIET can be electron sources to support anaerobic photosynthesis [7].…”
Section: Introductionmentioning
confidence: 99%
“…The proposed mechanism of DIET for these defined Geobacter species cocultures is that conductive pili from both Geobacter species facilitate the interspecific transfer of electrons with the help of cytochromes, which emphasizes the importance of the high conductivity of pili during DIET [9]. The importance of cytochromes in DIET is clear, such as the following: (i) the mutation of the abovementioned cytochromes inhibits the formation of cocultures; (ii) the DIET community, such as anaerobic bioreactors for treatment of brewery wastes [10], methanogenic digestion of wastewater [3] and rice paddy soils [11], always contains Geobacter species at high abundance, which take a hall-mark feature of abundance with c-type cytochromes [12]; (iii) The metagenome of proposed DIET-based consortia of anaerobic methane-oxidizing archaeal group 1 (ANME-1) methanotrophic archaea coupled to sulfate reduction contains abundant genes encoding multi-heme cytochromes [13]; (iv) in the DIET consortia of ANME-2 with its sulfate-reducing partner, regions with dense heme-staining in the multicellular assemblages are visualized indicating a cytochrome-based electron transfer between species [5]; and (v) the outer membrane surface cytochrome OmcB of G. sulfurreducens is necessary for syntrophic anaerobic photosynthesis [7].…”
Section: Introductionmentioning
confidence: 99%